Caracterização de isolados de Acidovorax avenae subsp. citrulli - OLIVEIRA, Janaína Cortêz de (2006)
The fruit blotch caused by Acidovorax avenae subsp. citrulli is the main bacterial disease of melon (Cucumis melo) in the Northeast of Brazil. In this work 49 isolates of A. avenae subsp. citrulli were studied aiming: to investigate the production of enzymes (pectinolytic, amylolytic, cellulolytic, lipolytic and proteolytic), phytohormone (indoleacetic acid), polysaccharide (levan) and toxin (syringomycin) by isolates of A. avenae subsp. citrulli and; to characterize this population based upon disease severity on seedlings, plants and fruits of melon and watermelon (Citrullus lanatus), hypersensitivity in tobacco (Nicotiana tabacum), utilization of amino acids as carbon and energy sources, and in vitro sensitivity to copper and antibiotics. All isolates of A. avenae subsp. citrulli produced lipase and indoleacetic acid, and none showed pectinolytic, amylolytic, cellulolytic and proteolytic activity nor produced levan and syringomycin. All isolatesinduced typical symptoms of fruit blotch on seedlings, plants and fruits of melon and watermelon. The Scott-Knott test (P = 0.05) separated the isolates for disease index in 5 and 7 groups respectively for melon and watermelon seedlings and 2 groups for plants of these two hosts. In fruits all isolates were separated in 3 and 10 groups for the variable diameter of extern lesion and 2 and 9 groups for lesion depth, respectively for melon and watermelon. All isolates also induced hypersensitivity in tobacco; utilized the amino acids asparagine, L-leucine and DL-acid lactic; showed sensitivity to copper oxychloride (120 μg ml-1), cuprous oxide (120 μg ml-1), copper hydroxide (138.2 μg ml-1), streptomycin sulfate (25 μg ml-1) and Agrimaicin 500 (428 μg ml-1); and resistance to kasugamycin (87 μg ml-1), agrimicin (200 μg ml-1), erythromycin (15 μg), gentamicin (10 μg), amoxicilin (10 μg), neomycin (30 μg) streptomycin (10 μg), norfloxacin (10 μg)and rifampicin (5 μg). Variability was found among the 41 isolates in relation toand rifampicin (5 μg). Variability was found among the 41 isolates in relation to